'There are Really Two Cities Here': Fragmented Urban Citizenship In Tel Aviv. (July 2015) - Cohen, Nir; Margalit, Talia
Abstract: The inflow of African migrants into Tel Aviv's southern neighborhoods has aroused much resentment from long‐term residents. Contesting the uneven burden sharing, which exacerbates already poor conditions at the local level, southern residents have aimed their grievances at municipal and national policymakers as well as the city's more affluent northern residents. In analyzing the contestation, this article challenges traditional conceptions of migrants as the binary opposition to residents of the host city, intruders on the shared and socio‐culturally homogenous urban arena. We build on recent theorizations of urban citizenship as an agency‐centered process to think through the ways in which city residents articulate their identities relationally and hierarchically against new and old 'others' and argue that international newcomers have destabilized long‐conceived social relations. Using narratives of long‐term southern residents, we illustrate how the uneven geographies of African migrants' settlement in Tel Aviv have (re)set in motion a process of urban citizenship formation by southern residents, thereby adding new layers of contention to what was already a highly stratified realm.